Psychometric Properties of Social Connectedness Scale - Soares, Ana Karla Silva; Goedert , Maria Celina Ferreira; Campanhã, Camila; Noriega, José Ángel Vera (Revista Interamericana de Psicología/Interamerican Journal of Psychology, 2023)
The perceived social connectedness (CS) is a one-dimensional construct conceptualized as the cognitive assessment that there is a close relationship with others, with whom contact can be made. This study aims to adapt the Social Connectedness Scale (SCS) to the Brazilian context, gathering evidence of psychometric adequacy. Two studies were conducted, the first (N = 285, mean age 24 years, SD = 4.92; 62% male) to obtain the exploratory factorial structure and the second (N = 300; mean age 23 years; SD = 5.43; 51% male) directed to confirmatory analysis of the unidimensionality and parameters of the item response theory. Internal consistency was satisfactory, as well as the evidence of convergent validity obtained from the negative correlations with the scale of depression, anxiety and stress. The results showed that the Portuguese version of the SCS gathered adequate psychometric evidence supporting its use in the measurement of SC.